2019
DOI: 10.1111/febs.14991
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical characterization and single‐chain Fv construction of a neutralizing antibody to measles virus

Abstract: The measles virus (MV) is a major cause of childhood morbidity and mortality worldwide. We previously established a mouse monoclonal antibody, 2F4, which shows high neutralizing titers against eight different genotypes of MV. However, the molecular basis for the neutralizing activity of the 2F4 antibody remains incompletely understood. Here, we have evaluated the binding characteristics of a Fab fragment of the 2F4 antibody. Using the MV infectious assay, we demonstrated that 2F4 Fab inhibits viral entry via e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
0
9
2
Order By: Relevance
“…While this loss of function should not exist in the wild, the question of the ability of such variants to invade the CNS which does not express SLAM or nectin-4 receptor under this selective pressure still needs to be investigated. More recently, neutralizing antibody-derived molecules such as single chain variable fragments targeting the H protein represent a major advance in the field of therapeutics design [252]. As for the corresponding neutralizing antibodies, the ability of such molecules to penetrate the brain parenchyma and to block hyperfusogenic variants depending less on the receptor engagement as those commonly observed in CNS infection has never been tested.…”
Section: Treatmentsmentioning
confidence: 99%
“…While this loss of function should not exist in the wild, the question of the ability of such variants to invade the CNS which does not express SLAM or nectin-4 receptor under this selective pressure still needs to be investigated. More recently, neutralizing antibody-derived molecules such as single chain variable fragments targeting the H protein represent a major advance in the field of therapeutics design [252]. As for the corresponding neutralizing antibodies, the ability of such molecules to penetrate the brain parenchyma and to block hyperfusogenic variants depending less on the receptor engagement as those commonly observed in CNS infection has never been tested.…”
Section: Treatmentsmentioning
confidence: 99%
“…V H and V L domains exhibit mutual stabilization due to their interaction, which depends on the intrinsic stability of each domain as well as the strength of their interface forces (35; 26). Many groups including Buhler et al, as well as our group, have previously reported that the domain orientation of scFv antibody had an impact on its biological and physicochemical properties, and production yield (1; 27). Thus, we first investigated one of the most commonly used FDA-approved mAbs, trastuzumab (Herceptin) (8; 14), for expression yield, thermal stability and antigen binding affinity of its V H -linker-V L (HL) and V L -linker-V H (LH) scFv forms.…”
Section: Resultsmentioning
confidence: 91%
“…The receptor binding site for measles virus H is considered a potential neutralization target. Neutralizing antibody-derived molecules such as single-strand variable fragments that target the H protein are possible candidates for treatment of SSPE [95]. In addition, small molecules such as the fusion-inhibiting peptide Z-D-L-Phe Gly [96] and AS-48 and 3G (analog of AS-48) inhibit membrane fusion in vitro [97,98].…”
Section: Preclinical Drugsmentioning
confidence: 99%